Alterations of the thrombin generation profile in rheumatoid arthritis - Kern Anita; Balog Attila; Dulic Sonja; Barabás Eszter; Kiszelak Mária; Vásárhelyi Barna (2016)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder resulting in the erosion of the cartilage and bone. Systemic involvement including the cardiovascular system with the risk of atherosclerosis may also occur. Calibrated automated thrombogram (CAT), a commercially available thrombin generation assay is suitable for the general assessment of the functionality of coagulation system. In this study we performed CAT assay in RA patients and in non-affected control subjects (matched for age, sex and comorbidities). Among the CAT parameters Velocity Index increased (from 60 to 83 nM/min), Lag Time and Time to Peak decreased (from 3.47 to 2.83 min and from 6.98 to 5.58 min respectively) in RA. On the other hand, Endogenous Thrombin Potential values decreased (from 1242 to 1108 nM min). The observed alterations were not associated with the applied therapy. These results indicate that the velocity of thrombin formation is increased, while the thrombin generating capability is reduced in RA.